Acute effects of barbell hip thrust on speed and power among volleyball athletes / Muhammad Fauzi Mohd Sunif ... [et al.]. - Mohd Sunif, Muhammad Fauzi; Mohd Nasir, Muhammad Zulqarnain; Abidin, Muhammad Amrun Haziq; Ahmad Tajri., Azman (2024)
This study investigates the acute effects of barbell hip thrust (BHT) on speed and power among volleyball athletes. Twenty-four volleyball players (N=24) were selected to become the subjects of this study. Subjects were divided into two groups: the experimental group (EG) and the control group (CG). Forty-meter (40-m) sprint test and vertical jump test were used to measure speed and power. The study involved the EG doing BHT exercises, and the CG performed regular training. The EG did 3 sets of 5 repetitions using 80% of their one-repetition maximum (1RM) for BHT, with a 3-minute rest between sets. The post-test was conducted 14 minutes after the intervention. Similar procedures were carried out for speed and power variables on different occasions. The results revealed a significant improvement in speed {t (22) = 2.18, p = 0.041, p < 0.05} and power {t (22) = 2.23, p = 0.037, p < 0.05} for the experimental group (EG) compared to the control group (CG). Specifically, the EG demonstrated a speed of 0.40 ± 0.11 sec, whereas the CG showed a speed of 0.30 ± 0.11 sec. Regarding power, the EG scored much higher, with 2.75 ± 0.67 cm, compared to the CG’s 2.22 ± 0.49 cm. These findings showed that the acute implementation of BHT can enhance speed and power in volleyball athletes and provide a valuable tool for volleyball training programs focusing on improving explosive performance.